Cardiovascular emergencies in primary care: an observational retrospective study of a large-scale telecardiology service - Marcolino, Milena Soriano; Santos, Thales Matheus Mendonça; Stefanelli, Fernanda Cotrim; Oliveira, João Antonio de Queiroz; Silva, Maíra Viana Rego Souza e; Andrade Júnior, Diomildo Ferreira; Silva, Grace Kelly Matos e (São Paulo Medical Journal, 2017)
BACKGROUND: Electrocardiograms (ECGs) are an essential examination for identification and management of cardiovascular emergencies. The aim of this study was to report on the frequency and recognition of cardiovascular emergencies in primary care units. DESIGN AND SETTING: Observational retrospective study assessing consecutive patients whose digital ECGs were sent for analysis to the team of the Telehealth Network of Minas Gerais. METHODS: Data from patients diagnosed with cardiological emergencies in the primary care setting of 750 municipalities in Minas Gerais, Brazil, between March and September 2015, were collected via telephone contact with the healthcare practitioner who performed the ECG. After collection, the data were subjected to statistical analysis. RESULTS: Over the study period, 304 patients with cardiovascular emergencies were diagnosed within primary care. Only 73.4% of these were recognized by the local physicians. Overall, the most frequent ECG abnormalities were acute ischemic patterns (44.7%) and the frequency of such patterns was higher among the ECGs assigned as emergency priority (P = 0.03). It was possible to obtain complete information on 231 patients (75.9%). Among these, the mean age was 65 ± 14.4 years, 57.1% were men and the most prevalent comorbidity was hypertension (68.4%). In total, 77.9% were referred to a unit caring for cases of higher complexity and 11.7% of the patients died. CONCLUSION: In this study, cardiovascular emergencies were misdiagnosed in primary care settings, acute myocardial ischemia was the most frequent emergency and the mortality rate was high.